PENGAWASAN UNIT PELAKSANA TEKNIS KESATUAN PENGELOLAAN HUTAN (UPT-KPH) SINGINGI: STUDI KASUS PADA AKSI ILLEGAL LOGGING DI KAWASAN HUTAN LINDUNG BUKIT BETABUH KABUPATEN KUANTAN SINGINGI TAHUN 2021 - Gusmarinda, Yolla; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is based on the existence of problems related to the continued occurrence of illegal logging activities such as forest encroachment, as well as the limited number of forest security personnel in the Bukit Betabuh Protected Forest Area. Therefore, this research aims to determine the supervision of the Singingi Forest Management Unit Technical Implementation Unit (UPT-KPH) on Illegal Logging in the Bukit Betabuh Protected Forest area, Kuantan Singingi Regency. This research uses a descriptive qualitative approach with data collection techniques including interview and documentation techniques. Then, the data analysis technique uses qualitative descriptive analysis techniques which include data collection, data reduction, data presentation and drawing conclusions. The results of this research show that the supervision carried out by UPT-KPH Singingi in dealing with illegal logging in the Bukit Betabuh Protected Forest area is still not optimal. Essentially, the absence of standard operating procedures (SOP) in monitoring patterns and the lack of human resources for the apparatus at the Environment and Forestry Service have become significant obstacles so that phenomena related to forest encroachment continue to occur repeatedly. In the process, this deficiency has hampered the implementation of work programs in the supervision sector, so that it has not reached the optimal level according to public expectations. Keywords : Supervision, Forest Areas, Protected Forests, Illegal Logging